Práticas de gamificação para uma cultura da sustentabilidade na educação profissional técnica de nível médio - Paiva, Suzana de Souza Damasceno (2024)
The gamification strategy has proven to be a promising practice in several sectors of society, the act of playing ends up being established in our perception of achievement. In this context, the research intention was to develop a study on gamification practices for the development of a culture of sustainability. In this way, the present work seeks to bring gamification as a strategy that promotes an educational practice that articulates the student's educational experience with their context, or educational practices that involve the interaction of the training process with socio-environmental urgency, thus being able to provide opportunities for meaningful experiences and contexts. of learning at EPTNM. This study is based on the line of research “Educational Practices in Professional and Technological Education”, whose bases are present in the macro-project “Methodological proposals and teaching resources in formal and non formal teaching spaces”. The objective is to evaluate the potential of gamification as an educational practice in building a culture of Sustainability at EPTNM. As specific objectives, the following are indicated: a) identify the perception of EPTNM participants regarding the gamification strategy; b) verify which gamification elements enhance sustainability practices; c) learn about possibilities for a culture of sustainability based on gamification at EPTNM; and d) produce a pedagogical game based on a culture of sustainability as an educational product. To this end, the Federal Institute of Amazonas – Campus Manaus Distrito Industrial (CMDI) was defined as the locus of study. Twenty (20) EPTNM students participated in this study. The methodological approach adopted was qualitative in nature, its materialization took place through field research with a multi-method approach. The techniques chosen were conversation circles, questionnaires, participant observation and workshops. These instruments helped in collecting data for the construction of this research with the aim of presenting proposals for the development of the work. After exploring the data, it was organized and analyzed through content analysis. As a result, a perception of gamification linked to the idea of games was observed, the elements of gamification that can enhance sustainability from the EPTNM context: contextualization, engagement and cooperation, as well as the indication of a culture of sustainability in the context of EPTNM. In the final stage, the construction of the Educational Product was allowed, entitled sustainable trail: a departure we want!